Arctic Studies A Proxy for Climate Change - Kanao, Masaki; Kakinami, Yoshihiro; Toyokuni, Genti (IntechOpen, 2019)
The Arctic region is the keystone to understanding the present status ofcurrently ongoing Earth systems and to predicting future imagesof our planet as viewed from northern high latitudes. The Arctic region,composed of ice-covered Arctic ocean in its center and surroundingfragmentation of the major continents, has been investigatedduring the last half century through all kinds of scientific studies:bioscience, physical sciences, geoscience, oceanography, and environmental studies, together with the technological domain. This book covers topics on the recent developments of all kinds of scientific research in and around the Arctic region, with a view to monitoring the current variations in the extreme environment, affected by remarkable changes in temperature and sea-ice extent, mass loss of ice-sheet and glaciers, and variations in marine and terrestrial ecosystems, including human activities.